THE CORELATION BETWEEN KNOWLEDGE OF SCANNING, SKIMMING, AND LOCAL FOLKLORE WITH COMPREHENDING NARATIVE TEXT - Handriano, .; Supardi, Iwan; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: The purpose of this research is to find out the correlation of scanning, skimming, and local folklore with comprehending narrative text to the eleventh grade students of SMAN 1 Sambas in academic year 2013/2014. This research was conducted as a correlation study by using four variables. The sample of this research were class XI class science II. The data were collected by using multiple choices consisting of fifteen items and questioner consisting of 6 questions, and were analyzed by using moment product Pearson formula. The finding shows that the correlation between the knowledge of skimming and scanning and local folklore material selection with comprehending narrative text is 0,18 or categorized as very low or negligible effect.. Keywords: Skimming, Scanning, Local Folklore, Comprehending Narrative Text Abstrak: Penelitian ini bertujuan untuk mengetahui sejauh mana korelasi antara pengetahuan tehnik membaca skimming, scanning dan cerita rakyat local dengan kemampuan memahami teks naratif terhadap siswa kelas XI SMAN 1 Sambas tahun ajaran 2013/2014. Penelitian ini dilakukan dengan menggunakan metode korelasi ganda dengan empat variabel. Sampel penelitian ini terdiri dari kelas XI IA 2. Data penelitian dikumpulkan melalui tes pilihan ganda yang berjumlah 15 soal dan kuesioner 6 soal dan data tersebut dianalisa dengan menggunakan rumus moment product pearson. Hasil penelitian menunjukan bahwa korelasi antara tehnik membaca skimming, scanning dan materi cerita rakyat lokal adalah 0,18 atau dikategorikan memiliki efek lemah atau hampir tidak ada. Kata kunci : Skimming, Scanning, Local Folklore, Pemahaman teks Narative